(untitled) (Al-Mithaq ( Research Journal of Islamic Theology), 2025)
This research article examines the authority (Ḥujjiyyah) of Taqrīrī Ḥadīth (tacit approval of the Prophet ﷺ) in Islamic jurisprudence and explores its related discussions among scholars. Taqrīrī Ḥadīth refers to instances where the Prophet ﷺ remained silent or expressed no objection to an action or statement made in his presence, signifying its permissibility in Islamic law. The study delves into classical and contemporary scholarly perspectives on the legal standing of such Aḥādīth, their role in deriving rulings, and their application in Fiqh al-Mu‘āmalāt and other areas of Islamic jurisprudence. Additionally, the article critically analyzes opposing viewpoints and addresses key questions regarding implicit endorsement versus explicit statements of the Prophet ﷺ. By examining various examples from authentic Ḥadīth collections and scholarly interpretations, this study aims to provide a comprehensive understanding of Taqrīrī Ḥadīth as a source of legal authority. The findings highlight its significance in shaping Islamic legal thought while also addressing concerns regarding contextual limitations and methodological considerations.